The effect of individual tree shelters in growth and morphology of cork oak seedlings - Dias, A. S.; Tomé, J.; Tavares, P.; Nunes, J.; Pereira, J. S. (SCIENTIA gerundensis, 1992)
To study the effects of the tree shelters in growth and morphology of cork oak ( Quercus suber L.) seedlings two types of plastic shelters were used in this work: A, transparent PVC shelters (brown) reinforced withawhitepolyesternet, 75 cmofheight; B, translucentbrownpolypropilene, double w$led, square cross section and 120 cm of height. The plants were grown in 120 cm long tubes in Evora, Portugal and growth of sheltered and control plants was evaluated based upon measurements of height, branch lenght, number and area of leaves and biomass. Additionally the anatomy and morphology and heat tolerance of leaves of sheltered andcontrolplants was studied. The results sbow that prowth in beight was stimulated by shelters. The amount of branches was greater in seedlings with shelters seedlings in shelters B were not significant. The shootíroot ratio was higher in sheltered plants than in controls because of the above-ground biomass increased in the former whereas root biomass remained unchanged. Foliage developed inside the shelters showed characteristics of acclimation to shade and were less tolerant to heat being killed at lower temperatures than those of unsheltered controls. A than in controls but the differences between the latter and
Keywords: Acclimation to shade; heat tolerance; Quercus suber; tree shelters